The Use of E-Book Learning in Arabic Language Instruction to Improve Reading Skills - Nanang Kosim; Ade Arip Ardiansyah; Rina Yulianingtiyas Hajir; Neneng Novita Aulia; Putri Nabila; Pahmi Paturohman; R. Muhammad Hasbi Albar Romli (UIN Sunan Gunung Djati Bandung, 2025)
This study was motivated by the low level of students’ Arabic reading skills among seventh-grade students at MTs Islam Bakti Asih. One of the main contributing factors is the limited availability of engaging and appropriate instructional media. To address this issue, this study implemented E-book-based learning as an instructional medium to improve students’ reading skills. This research employed a Classroom Action Research (CAR) design conducted in two cycles. The participants consisted of 24 students from class VII A. The instructional process used a cooperative learning model to promote student interaction and collaboration. Each cycle included four stages: planning, action, observation, and reflection. Data were collected through observation, pre-tests and post-tests, and documentation, and were analyzed using both quantitative and qualitative descriptive techniques. The results revealed a significant improvement in students’ reading skills following the implementation of E-book learning. Initial improvement was observed in the first cycle, with further enhancement evident in the second cycle, as indicated by the increasing number of students meeting the minimum mastery criteria. Therefore, integrating e-book learning within a cooperative learning framework proved effective in enhancing students’ Arabic reading skills.